Pemahaman dan Pengenalan Qanun Hukum Jinayat Bagi Masyarakat Daerah Terpencil di Aceh Utara (Studi Penelitian di Desa Alue Leuhop dan Cot Girek Kec. Cot Girek Kab. Aceh Utara) (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
This article attempts to research and seek answers to the following problems, How is the understanding of the people of Alue Leuhop and Cot Girek villages towards the Jinayat Law (Qanun Jinayat); How is the existence and implementation of the Jinayat Law (Qanun Jinayat) in the midst of the Alue Leuhop Village Community and Cot Girek Village; What efforts should be made by the Related Parties to improve community understanding and recognition of the Jinayat Law (Qanun Jinayat)?This research concludes, a). Alue leuhop and Cot village communities are enthusiastic, basically there is still very little information about jinayat law so that it is lacking in understanding even the people in general do not get enough informations about jinayat law. b). Law carried out in the midst of the community still revolves around the implementation of local customary law so that the jinayat law is not used by those people. c). Socialization and introduction of jinayat law by the Regency government or related parties (Subdistrict, Sharia Office) is very necessary because the people do not understand the jinayat law because they do not have reading material or knowledge about jinayat law practice.